Pemanfaatan Media Gambar Terhadap Peningkatkan Hasil Belajar IPS Pokok Bahasan Produksi Komunikasi Kelas IV SD - Krisnawati Krisnawati (Journal on Education, 2024)
This research aims to determine the increase in social studies learning outcomes on the subject of communication production using image media for fourth grade elementary school students. This research was carried out at SDN 3 Nganganaumala. The approach to this research used a mix method by presenting it in qualitative descriptive form and then proving it in quantitative form. The population of this study were all students at SDN 3 Nganganaumala. Meanwhile, the research sample was 25 class IV students at SDN 3 Nganganaumala. The sample was carried out using purposive sampling, namely by taking samples with consideration of aspects. Based on the results of research in the pre-cycle, there were 6 students showing complete grades and 19 students showing incomplete grades, while in the first cycle 10 students showed complete grades and 15 students showed incomplete grades, while in the second cycle there was an increase in learning outcomes, 20 students showed complete grades and 5 students showed incomplete grades. complete.